Systemic fungal endophytes and ploidy level in Festuca vivipara populations in North European Islands - P. E. Gundel; S. Dirihan; M. Helander; I. Zabalgogeazcoa; H. Väre; K. Saikkonen (SPRINGER WIEN, 2022)
Exploring the regional pattern of variation in traits driven by symbiotic interactions may provide insights to understand the evolutionary processes that operate over plant populations. Polyploidy, which is associated with fitness improvement, is expected to increase with latitude and altitude. However, it has never been explored in relation with the occurrence of epichloid fungal endophytes in plants. Both, variation in ploidy level and in the incidence of fungal endophytes, are known to occur in species of fine fescues. Here, we surveyed the occurrence of systemic fungal endophytes in natural Festuca vivipara populations in North European islands. In addition, we identified the fungal species associated with this grass and determined the predominant ploidy level for each population. Endophytes were found in four of six, two of three, and one of three populations for Faroe Islands, Iceland and Great Britain, respectively. With an average low incidence level of 15 % in infected populations, there was no relationship between infection level and either latitude or altitude. The phylogenetic analysis based on sequences ITS and the tub2 genes, supports that the endophytic species is EpichloA << festucae, the same as in other fine fescues. We found no variation in ploidy level as all the plants were tetraploid (4X) with 28 chromosomes, a pattern which contrasts with the variation reported in previous antecedents. Our results suggest that apart from low and variable benefits of the endophyte to the plants, there would be a complex dynamics between epichloid endophytes and species of the fine fescue complex which merits further studies.